Femtosecond laser polishing with high pulse frequency for improving performance of specialised aerospace material systems: MCrAlY coatings in thermal barrier coating system. (November 2022) - Qian, Wei; Cai, Jie; Xin, Zhiduo; Ye, Yunxia; Dai, Fengze; Hua, Yinqun
Abstract: MCrAlY coatings are widely used as bond coats in thermal barrier coating system to protect thermally loaded structures from oxidation during high-temperature service. Surface roughness (Sa) and microstructures are essential for high-temperature oxidation resistance of MCrAlY coatings. Despite the successful use of laser polishing with long pulse durations for surface modification of alloys, inevitable excessive ablation of the material limits its application to smoothing of MCrAlY coatings. In this study, a novel polishing technique based on remelting was developed via femtosecond laser polishing with high pulse frequency (FLPHPF). Different single pulse fluence and scanning trajectories were performed, and mechanisms of melt-condensation and polishing effect induced via FLPHPF were investigated. Microstructural observations revealed that FLPHPF treatment could reduce Sa, refine grains, introduce dislocations, and change elemental distributions. The restructured and polished remelted layer contributed to a thinner, continuous, and uniform α-Al2 O3 scale during the oxidation process, which verifies that FLPHPF technique is an effective and feasible method to improve the high-temperature oxidation resistance of MCrAlY coatings. Based on this research, a laser polishing technique with low ablation and controlled thermal accumulation was proposed. Moreover, FLPHPF broadens the application prospects of ultrashort pulse lasers and provides an alternative processing strategy for the surface modification of ultra-thin fine structures. Graphical abstract: Image 1 Highlights: MCrAlY coatings were treated using a novel FLPHPF technique. Coating was polished by controlling laser parameters without excessive ablation. Microstructural reconstruction and elemental redistribution of coating were obtained. Restructuring of surface contributed to a tinner, continuous and stable Al2 O3 scale. FLPHPF technique is an effective way to extend the service life of MCrAlY coatings.